Factors Related to The Performance of Health Workers at The Inerie Public Health Center, Ngada Regency - Theofilus Suri; Erny Erawati Pua Upa; Rina Waty Sirait (Media Kesehatan Masyarakat, 2022)
Performance is a person's success during a certain period in doing work according to work standards and targets or targets that have been mutually agreed upon. Performance is influenced by various factors including work motivation, work environment, rewards, work discipline, and organizational culture. This study aims to identify factors related to the performance of health workers at the Inerie Public Health Center, Ngada Regency in 2020. The method used in this study is a quantitative study using a cross-sectional approach. The sample size is 35 people. The data were analyzed by univariate and bivariate and tested by chi-square statistical test. The results showed that there was a relationship between the work performance of health workers (0.001), awards (0.002), work environment (0.003), work discipline (0.027), organizational culture (0.031) with the performance of health workers at the Inerie Public Health Center, Ngada Regency. The performance of health workers at the Inerie Health Center has been good in providing services to the community.